2010
DOI: 10.1073/pnas.0906764107
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the Wnt pathway, a unifying mechanism for an angiogenic inhibitor in the serine proteinase inhibitor family

Abstract: The Wnt pathway regulates multiple biological and pathological processes including angiogenesis and inflammation. Here we identified a unique inhibitor of the Wnt pathway, SERPINA3K, a serine proteinase inhibitor with anti-inflammatory and angiogenic activities. SERPINA3K blocked the Wnt pathway activation induced by a Wnt ligand and by diabetes. Coprecipitation and ligand binding assay showed that SERPINA3K binds to low-density lipoprotein receptor-like protein 6 (LRP6) with a K d of 10 nM, in the range of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
75
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 49 publications
4
75
0
2
Order By: Relevance
“…Previous studies have identified a number of proteins which regulate Wnt signaling through binding to LRP6, including the DKK family, endostatin, and IGFBP4 (47,79,83). Recently, we have shown that another angiogenic factor, SERPINA3K, a member of serine proteinase family which shares 84% sequence homology with PEDF, also binds to LRP6 (78). Considering the complexity of Wnt pathway regulation and its interactions with other pathways, it is possible that the lack of severe developmental defects in PEDF-TG and PEDF Ϫ/Ϫ mice may be ascribed to compensation from other Wnt pathway modulators or from other signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a number of proteins which regulate Wnt signaling through binding to LRP6, including the DKK family, endostatin, and IGFBP4 (47,79,83). Recently, we have shown that another angiogenic factor, SERPINA3K, a member of serine proteinase family which shares 84% sequence homology with PEDF, also binds to LRP6 (78). Considering the complexity of Wnt pathway regulation and its interactions with other pathways, it is possible that the lack of severe developmental defects in PEDF-TG and PEDF Ϫ/Ϫ mice may be ascribed to compensation from other Wnt pathway modulators or from other signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of this antibody into Akita mice inhibited the activation of the WNT pathway and ameliorated diabetic nephropathy as shown by fibrogenic factor production, extracellular matrix accumulation and proteinuria. Meanwhile, delivery of serine (or cysteine) peptidase inhibitor, clade A, member 3K (SERPINA3K), an endogenous antagonist of LRP6 [42], also reduced albuminuria in db/db mice (Electronic supplementary material [ESM] Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…As an angiogenic inhibitor, SERPINA3K was found to downregulate several pro-angiogenic cytokines such as CTGF and VEGF, which are also target genes of the Wnt pathway (Zhang et al, 2009(Zhang et al, , 2010a. In experimental diabetic models, SERPINA3K blocked Wnt signaling activation in the retinas with microvascular complications and in cells treated with high glucose, suggesting that SERPINA3K may regulate angiogenesis through interacting with the Wnt pathway (Zhang et al, 2010a, b).…”
Section: Serpina3kmentioning
confidence: 99%
“…In experimental diabetic models, SERPINA3K blocked Wnt signaling activation in the retinas with microvascular complications and in cells treated with high glucose, suggesting that SERPINA3K may regulate angiogenesis through interacting with the Wnt pathway (Zhang et al, 2010a, b). Further, SERPINA3K was identified as a Wnt antagonist since it blocked the Wnt ligandinduced Wnt pathway activation, blocking phosphorylation of LRP6, cytosolic β-catenin stabilization, TCF/LEF-mediated transcription activity and Xenopus axis duplication.…”
Section: Serpina3kmentioning
confidence: 99%